The Perceived Professional Development among EFL Cambodian Lower Secondary Teachers - Siem Or (MASI Mandiri Edukasi, 2025)
This study examines the involvement of Cambodian EFL teachers in decision-making related to professional development in lower secondary schools in Phnom Penh. Using an exploratory research design, data were collected through questionnaires from 40 teachers and semi-structured interviews with six participants. The study examines how Cambodian EFL teachers perceive their role in shaping professional growth activities, including training and workshops. Findings reveal that teachers’ participation is minimal, unstructured, and largely directed by top-down decisions. Five major themes emerged: lack of professional development opportunities, limited systematic and customized involvement, inadequate professional tools, insufficient institutional support, and teachers’ discontent with their growth prospects. These issues contribute to a weak professional learning culture and a sense of exclusion. This study contributes to understanding teacher agency and professional growth in developing contexts. It emphasizes the need for systemic reform in educational policy and school leadership to foster more inclusive, collaborative, and teacher-centered professional development systems that enhance motivation, agency, and educational outcomes. Future research should include focus groups to gain deeper insights and expand across different regions and types of schools, thereby providing a more comprehensive understanding of teacher involvement in decision-making.